2015
DOI: 10.1094/pdis-10-14-1025-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Pantoea anthophila Causing Soft Rot Disease in Clausena lansium (Wampee) in China

Abstract: Clausena lansium, also known as wampee (Clausena wampi), is a plant species native to China, Vietnam, the Philippines, Malaysia, and Indonesia, where it is widely cultivated, and also grown in India, Sri Lanka, Queensland, Florida, and Hawaii, but less frequently (3). The fruit can be consumed fresh or made into juice, jam, or succade. In summer to fall 2014, a soft rot disease was found in a wampee planting region in Yunan County, Guangdong Province, China. On Sept. 18, we collected diseased samples from a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3.1 Endophytic Pantoea anthophila P. anthophila was previously reported in eucalyptus and maize and also found to cause infections in Impatiens balsamina, Tagetes erecta and Clausena lansium [28,29]. The multidimensional property of endophytes may produce stable nanoparticles with high medicinal potency, hence the extracelluar metabolite rich broth of P. anthophila are utilised for Pa-AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…3.1 Endophytic Pantoea anthophila P. anthophila was previously reported in eucalyptus and maize and also found to cause infections in Impatiens balsamina, Tagetes erecta and Clausena lansium [28,29]. The multidimensional property of endophytes may produce stable nanoparticles with high medicinal potency, hence the extracelluar metabolite rich broth of P. anthophila are utilised for Pa-AgNPs synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Wan et al reported the draft genome sequence of P. anthophila strain 11-2 isolated from hypersaline water from the lake on Laysan, Hawaii and numerous virulence-related components were identified based on bioinformatic analysis (Wan et al, 2015). Only one study by Zhou et al reported for the first time that P. anthophila naturally caused soft rot disease and cracking on C. lansium (Zhou et al, 2015), indicating that P. anthophila is pathogenic to plant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Brady et al placed this strain into a separate cluster and proposed its current name as P. anthophila by using multilocus sequence analyses (MLSAs), amplified fragment length polymorphism (AFLP) analysis, and DNA-DNA hybridization in 2009 (Brady et al, 2009). Upon searching in PubMed, only one study reported that P. anthophila is pathogenic to plants and naturally causes soft rot disease and cracking on Clausena lansium (wampee) in China (Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wampee is a perishable fruit, which is susceptible to mechanical damages, browning, and disease infection after harvest (Shao et al, 2020 ). Meanwhile, pathogen invasion as a factor-causing fruit softening and cracking has been a concern in wampee fruit production (Zhou et al, 2015 ). It has been widely reported that the chemical composition and the structural arrangements of the cell wall or cuticle, as well as the fruit surface properties, are pivotal in maintaining the fruit quality (Ríos et al, 2015 ; Winkler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%